Management of stent underexpansion using intravascular lithotripsy—Defining the utility of a novel device. Issue 1 (8th January 2020) - Yeoh, Julian; Cottens, Daan; Cosgrove, Claudia; Mallek, Khaled; Strange, Julian; Anderson, Richard; Wilson, Simon; Hanratty, Colm; Walsh, Simon; McEntegart, Margaret; Hill, Jonathan; Spratt, James C.
Abstract: Objectives: This study aimed to present a case series of patient treated for stent underexpansion resistant to conventional treatment with intravascular lithotripsy (IVL). Background: Stent underexpansion is a powerful predictor of long‐term stent patency and correlates with unfavorable clinical outcomes. This case series demonstrates the utility of IVL in managing stent underexpansion resistant to conventional treatment. Methods: We describe a case series of patients with stent underexpansion due to calcific coronary artery disease treated with IVL. Stent underexpansion was identified as an inability to adequately expand stents with conventional treatment. Only cases that failed to achieve adequate expansion with high‐pressure noncompliant balloon inflation were included. Results: Thirteen patients from six institutions have been included in this case series. The average age was 70.25 years with 76.9% of male patients. The average pre‐IVL minimal stent area (MSA) was 2.71 mm 2, which improved to 6.44 mm 2 post‐IVL treatment, representing an average MSA gain of 238%. There were no procedural, peri‐procedural, or 30‐day major adverse cardiac and cerebrovascular event. Conclusion: This case series demonstrates that IVL is a feasible, safe alternative for the management of stent underexpansion due to calcific coronary disease.